Networking Society, Networks Based Economy and the Processes of Global Social, Economic and Technological Changes - Melnikas, Borisas (Ekonomika, 2016)
Processes and problems of the creation of networking society and network-based economy are described in this theoretical article. Networking processes and the network-based new development tendencies in various sectors of economy and social life in the context of contemporary global changes are defined as an especially important field of the scientific research and studies. The main aspects of the networking and network-based development tendencies are analysed. The complexity and systematics of the networking processes and the networking society creation under conditions of globalisation and contemporary changes in various areas of social and economic life are analysed. The main attention is focused on the idea that networking processes and the creation of networking society and network-based economy could be perceived as one of the most important priorities of the modernisation of contemporary social and economic systems, as well as of social, economic, political development, science, and technological progress in general. The creation of networking society and network-based economy is assessed as the most important assumption and the main way to solve most of the social, economic, technological, even security, defence and ecological problems worldwide, as well as in various countries or regions in general and in various countries or regions in the space of the European Union. The processes of the creation of networking society and network-based economy express the essential qualitative changes in all areas of social, economic, political life, science, and technological progress, and interaction with nature. The processes of the creation of networking society and network-based economy deeply influence the content of globalisation and internationalisation processes and the effect on a situation in the modern world. The processes of the creation of networking society and network-based economy must be analysed in complexity. This analysis should be orientated towards the systematically examined and assessed changes and development processes. It is particularly important that the processes of the creation of networking society and network-based economy are taking place on a global scale and could be defined as the processes belonging to the category of global processes and changes: it also means that the complex interaction between the processes of global changes and the processes of the creation of networking society and network-based economy is a very important factor of the positive development in the societal life in the general context of globalisation. Problem is that the networking society and the network-based economy creation processes and other processes of global changes are usually analysed separately: the factor of the complex interaction between different global processes and the processes of the creation of networking society and network-based economy is often ignored. It means, that a complex analysis of the processes of various types, as well as an evaluation of the factors of interaction between different processes could be defined as a perspective way to solve some actual theoretical and practical problems of the development of contemporary economy and of the creation of networking society and network-based economy in general, especially in the context of globalisation. The complex analysis and the multidimensional evaluation of the general processes of global changes and of the specific processes of networking society and the network-based economy creation as a perspective theoretical approach in research on societal changes in the context of globalisation is defined and described in this theoretical article. The variety and the main phenomena and regularities of the global changes are identified, their impact on real processes of networking society and network-based economy creation is characterised. The main principles of the networking society and the network-based economy creation in the context of global changes are formulated. The main idea of the complex analysis and of the evaluation of the factors of interaction between different processes of global changes and the processes of networking society and network-based economy creation could be briefly described as follows: the complex analysis and evaluation of these factors includes two aspects – first, all these processes should be defined and analysed as the global changes in general, secondly, the processes of the creation of networking society and networks based economy should be identified as an specific and especially important priority of contemporary social, economic, organizational and technological changes in the global space. This idea is described in details in the article.